Estudos da tolerância à dessecação em sementes de espécies florestais nativas oriundas do Norte de Mato Grosso - Pelissari, Fabieli (2013)
The seeds are the main form of propagation of plant species, especially the forest one. Therefore, the study and understand the physiological processes related to seeds is critical to establish the best techniques for storage, preservation, germination and propagation of the species. Thus, this study aimed to classify Parkia pendula, Parkia platycephala, Parkia multijuga, Amburana acreana and Myracrodruon urundeuva while the ability of desiccation tolerance and storage. All seeds were collected in Sinop and the analysis were performed at the Seed Analysis Laboratory of the Federal University of Mato Grosso, Campus Sinop. The orthodox seeds, unlike the recalcitrant, can be stored for long time without lost of viability, being the understanding of behavior during the storage required for choosing the right strategy for their conservation. Once those individuals of the same species, but from different regions, may present different performance in different temperature conditions, it was carried out a study about germination behavior of seeds from five species at different controlled temperatures conditions (chamber BOD). Dormant seeds were tested for scarification methods, facilitating water absorption and germination. The best method of scarification and temperature was used to perform the tests of desiccation tolerance and storage. No differences were observed in seeds of species A. acreana and M. urundeuva in all temperatures tested (25°C, 30°C and 25-30°C). However, P. pendula, P. platycephala and P. multijuga seeds presented integumentary dormancy. Mechanical scarifications are recommended on electric emery to overcome seed dormancy of de P. pendula and P. platycephala, and mechanical scarification on electric emery followed by immersion in water for 24 hours for P. multijuga. The temperature of 30°C is recommended for the three species during the test germination. All species showed orthodox behavior, supporting desiccation to levels close to 0.05 gH2O/gMS and storage in negative temperatures.